Fizika, 2. del: zbrano gradivo - Padežnik Gomilšek, Jana; Hauko, Robert (University of Maribor Press, 2017)
Physics, Part 2: Textbook. The textbook Fizika, 2. del (Physics, Part 2) is intended for the first level students at the Faculty of Mechanical Engineering of University of Maribor, predominantly for the subject Waves and material structure in the summer semester of the first year. It contains chapters: Oscillatory motion, Mechanical waves, Optics, Photon, Atom, Molecules and crystals, and Atomic nucleus. The textbook with a lot of examples helps students to prepare for the exam. It also contains some topics which are skipped in the classroom due to lack of time.